2020
DOI: 10.5194/acp-20-9351-2020
|View full text |Cite
|
Sign up to set email alerts
|

Scattered coal is the largest source of ambient volatile organic compounds during the heating season in Beijing

Abstract: Abstract. We identified scattered coal burning as the largest contributor to ambient volatile organic compounds (VOCs), exceeding traffic-related emissions, during the heating season (the cold season when fossil fuel is burned for residential heating) in Beijing prior to the rigorous emission limitations enacted in 2017. However, scattered coal is underestimated in emission inventories generally because the activity data are incompletely recorded in official energy statistics. Results of positive matrix factor… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 92 publications
(110 reference statements)
0
19
0
Order By: Relevance
“…Although some studies showed that N 2 O 5 heterogeneous processes on a high Cl – aerosol surface might be important pathways to nitrate formation, ,, this reaction would also result in a higher ClNO 2 yield and thus decrease the nitrate aerosol formation . Thus, the high nitrate concentration in the winter was mainly due to the active NO 3 + HC reaction on the basis of higher concentrations of volatile organic compounds (VOCs) via additional fossil fuel emissions. , Our results highlighted that the nocturnal chemistry (NO 3 radical chemistry, NO 3 + HC and N 2 O 5 + H 2 O/Cl – ) dominated nitrate production during the winter, while the OH/H 2 O + NO 2 pathway and nighttime pathways contributed equally to nitrate formation during the summer. Recent studies have pointed out that NO 3 + HC and N 2 O 5 hydrolyses were major formation mechanisms of nitrate production and were much greater in cold seasons on the basis of oxygen isotope observations.…”
Section: Resultsmentioning
confidence: 69%
See 1 more Smart Citation
“…Although some studies showed that N 2 O 5 heterogeneous processes on a high Cl – aerosol surface might be important pathways to nitrate formation, ,, this reaction would also result in a higher ClNO 2 yield and thus decrease the nitrate aerosol formation . Thus, the high nitrate concentration in the winter was mainly due to the active NO 3 + HC reaction on the basis of higher concentrations of volatile organic compounds (VOCs) via additional fossil fuel emissions. , Our results highlighted that the nocturnal chemistry (NO 3 radical chemistry, NO 3 + HC and N 2 O 5 + H 2 O/Cl – ) dominated nitrate production during the winter, while the OH/H 2 O + NO 2 pathway and nighttime pathways contributed equally to nitrate formation during the summer. Recent studies have pointed out that NO 3 + HC and N 2 O 5 hydrolyses were major formation mechanisms of nitrate production and were much greater in cold seasons on the basis of oxygen isotope observations.…”
Section: Resultsmentioning
confidence: 69%
“…17 Thus, the high nitrate concentration in the winter was mainly due to the active NO 3 + HC reaction on the basis of higher concentrations of volatile organic compounds (VOCs) via additional fossil fuel emissions. 38,66 Our results highlighted that the nocturnal chemistry (NO 3 radical chemistry, NO Interestingly, different vertical patterns of the reactions and nocturnal pathways were found during the distinct sampling periods. In the wintertime, the OH/H 2 O + NO 2 fractions at 8 m (41%) and 120 m (36%) were significantly higher than that at 260 m (20%), which might be attributed to higher NO 2 emissions at the ground surface.…”
mentioning
confidence: 69%
“…Emission inventory estimates of NMVOCs are subject to large uncertainties, mainly due to poorly quantified industrial emissions (Li et al, 2017) and lack of reliable data for scattered areal sources such as residential coal burning (Li et al, 2019c;Peng et al, 2019;Shi et al, 2020). We find though that modelled CO is relatively unaffected by NMVOCs emissions.…”
Section: Squires Et Al (mentioning
confidence: 79%
“…The decrease of CO 2 in March 2019 is highly related to the temperature increase. As the heating is officially stopped in the middle of March, the anthropogenic emissions are much reduced (Shi et al, 2020). In April and May, the LAI increases monthly means of CO2 together with the 1σ standard deviation at BJ L1, XH L1 and XL between June 2018 and February 2020.…”
Section: Seasonal Variationsmentioning
confidence: 99%